Long-term population trends and habitat preferences of waders at Strandfontein wastewater treatment works - Essig, Erica Carla (Department of Biological Sciences, 2017)
The aims of the dissertation are to describe long term migrant and residential wader population trends at Strandfontein, and to identify the potential factors which influence local wader abundance. Once identified, these factors are integrated into a management plan that would create ideal wader habitat, and attract larger numbers of waders to Strandfontein.